Heterozygote Advantage Probably Maintains Rhesus Factor Blood Group Polymorphism: Ecological Regression Study - Flegr, Jaroslav (PloS one, 2016)
Rhesus factor polymorphism has been an evolutionary enigma since its discovery in 1939. Carriers of the rarer allele should be eliminated by selection against Rhesus positive children born to Rhesus negative mothers. Here I used an ecologic regression study to test the hypothesis that Rhesus factor polymorphism is stabilized by heterozygote advantage. The study was performed in 65 countries for which the frequencies of RhD phenotypes and specific disease burden data were available. I performed multiple multivariate covariance analysis with five potential confounding variables: GDP, latitude (distance from the equator), humidity, medical care expenditure per capita and frequencies of smokers. The results showed that the burden associated with many diseases correlated with the frequencies of particular Rhesus genotypes in a country and that the direction of the relation was nearly always the opposite for the frequency of Rhesus negative homozygotes and that of Rhesus positive heterozygotes. On the population level, a Rhesus-negativity-associated burden could be compensated for by the heterozygote advantage, but for Rhesus negative subjects this burden represents a serious problem.
Keywords: Humans; dítě; polymorfismus genetický; Homozygote; Child; Female; frekvence genu; krevní skupiny - systém Rh-Hr; Genotype; lidé; Rh-Hr Blood-Group System; Regression Analysis; Polymorphism, Genetic; homozygot; ženské pohlaví; Male; Genetic Predisposition to Disease; genetická predispozice k nemoci; Gene Frequency; Heterozygote; genotyp; heterozygot; míra přežití; mužské pohlaví; regresní analýza; Survival Rate